2001
DOI: 10.1093/aje/154.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Breastfeeding and the Prevalence of Asthma : The Tokorozawa Childhood Asthma and Pollinosis Study

Abstract: Many risk factors for asthma have been proposed including age, gender (male), smoking, and family history of asthma. The importance of breastfeeding to childhood asthma is a controversial issue. The present study investigated the relation between breastfeeding and the prevalence of asthma among a childhood population. The subjects were 25,767 students, representing all public elementary and junior high schools in Tokorozawa, Japan (age range, 6--15 years). The study population included 2,315 students with asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
3
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 22 publications
8
53
3
3
Order By: Relevance
“…Similarly it was reported previously also that prevalence of asthma was low in children with exclusive breast feed compared to infants with partial breast feeding and formula milk [40][41][42]. Unlike these results, higher prevalence of asthma was found among children who had been breastfeed [43] and also reported that breastfeeding does not protect children against atopy and asthma and may even increase the risk [44]. Likewise, we observed caesarean mode of delivery was found significantly associated with asthma risk, as reported earlier also [45,46].…”
Section: Discussionsupporting
confidence: 48%
“…Similarly it was reported previously also that prevalence of asthma was low in children with exclusive breast feed compared to infants with partial breast feeding and formula milk [40][41][42]. Unlike these results, higher prevalence of asthma was found among children who had been breastfeed [43] and also reported that breastfeeding does not protect children against atopy and asthma and may even increase the risk [44]. Likewise, we observed caesarean mode of delivery was found significantly associated with asthma risk, as reported earlier also [45,46].…”
Section: Discussionsupporting
confidence: 48%
“…Two meta-analyses (4,5) and a recent study in New Zealand (6) reported that breastfeeding continued to be associated with decreased risk of asthma in children after cessation of breast-feeding. However, a large-scale randomized trial (7) and several observational studies (8)(9)(10)(11) found no effect or even an increased risk of asthma. The Japanese Pediatric Guideline for Food Allergy concluded that evidence was insufficient that exclusive breast-feeding had more preventive effects on allergy than partial breast-feeding (12) .…”
Section: Breast-feeding Asthma Childmentioning
confidence: 99%
“…Although breast-feeding has long-term benefits for children's health such as prevention of overweight/obesity and type 2 diabetes and improvement of cognitive function (1) , the protective effect of breast-feeding on asthma in childhood still remains controversial (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) . Two meta-analyses (4,5) and a recent study in New Zealand (6) reported that breastfeeding continued to be associated with decreased risk of asthma in children after cessation of breast-feeding.…”
Section: Breast-feeding Asthma Childmentioning
confidence: 99%
“…Breastfeeding itself decreases early childhood wheezing syndromes associated with upper and lower respiratory infections. However, although recommended for its general health benefits, there is little evidence that breastfeeding prevents development of persistent asthma 9,[23][24][25] .…”
Section: Maternal Diet During Pregnancy And/or Lactationmentioning
confidence: 99%